2015
DOI: 10.1007/s10236-015-0899-6
|View full text |Cite
|
Sign up to set email alerts
|

Local inertial oscillations in the surface ocean generated by time-varying winds

Abstract: A new relationship is presented to give a review study on the evolution of inertial oscillations in the surface ocean locally generated by time-varying wind stress. The inertial oscillation is expressed as the superposition of a previous oscillation and a newly generated oscillation, which depends upon the time-varying wind stress. This relationship is employed to investigate some idealized wind change events. For a wind series varying temporally with different rates, the induced inertial oscillation is domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Based on the best track data from CMA, the translation speed of Meranti around 0000 UTC + 8 9 September was approximately 3.6–4.8 m/s, whereas that of Megi around 0000 UTC + 8 22 October was approximately 2.3–3.1 m/s. According to S. Chen et al (), the intensity of NIWs increases with typhoon translation speed if the translation speed is smaller than a critical value and falloff otherwise. At 21°N, the critical value is approximately 4–5 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the best track data from CMA, the translation speed of Meranti around 0000 UTC + 8 9 September was approximately 3.6–4.8 m/s, whereas that of Megi around 0000 UTC + 8 22 October was approximately 2.3–3.1 m/s. According to S. Chen et al (), the intensity of NIWs increases with typhoon translation speed if the translation speed is smaller than a critical value and falloff otherwise. At 21°N, the critical value is approximately 4–5 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting phenomenon is found in which the weaker typhoon Meranti generates stronger NIWs than the stronger typhoon Megi. By analyzing the typhoon translation speed using the best track data from CMA, the larger translation speed of Meranti may be a cause of the phenomenon, according to S. Chen et al (). Guan et al () also suggested that Megi could reinforce the D1 energy in the surface layer, which affected the energy imported to the NIWs and may be another possible cause of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of turbulence by shear across the TL is particularly efficient when the rate at which near-surface winds rotate due to the motion of a storm, matching the inertial period of the wind-driven currents (Large and Crawford 1995;Dohan and Davis 2011;Chen et al 2015). This resonance condition allows large shears to build at the base of the well-mixed layer, which can lead to the growth of a stratified shear layer below the WML, without significant impact on the thickness of the WML (Dohan and Davis 2011;Johnston et al 2016;Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For a specified stratification and fixed latitude, the maximum of the internal wave power always presents an optimal turn with the speed of the hurricane. Chen et al [18] subsequently pointed out that the oceanic near-inertial response arises when the wind speed increases or with a closer frequency to the inertial frequency at a fixed point. Meanwhile, the amplitude of oceanic inertial oscillation increases with increasing translation speed, due to the higher local rotation frequency, but a faster cyclone has shorter influence duration, which may lead to less oceanic near-inertial energy induced in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The rightward bias is usually attributed to the resonance effect via the air-sea interactions, i.e., the wind stress vectors on the right (or left) of the cyclone track turn clockwise (or anticlockwise) and resonate with typhoon-generated oceanic currents, resulting in more (or less) intensive kinetic energy generated in the upper ocean. When the rotation rate of resonant near-inertial oceanic currents matches the local inertial frequency, the maximal amplitude of inertial oscillations is generated [18,24,25].…”
Section: Introductionmentioning
confidence: 99%